Review on Malaysia Tax Performance: Rates and Land Tax - Norfaizah Sahari , Siti; Samsuddin, Salfarina; Ariffian Bujang, Ahmad; Suratman, Robiah; Shahril Abd Rahman, Mohd; Rangga Anthony Jiram, Wilson (International Journal of Psychosocial Rehabilitation, 2020)
Rates and land tax are the most important taxes in contributing to the financial sustainability and function of a government, either at the state or local authority level of Malaysia. The aim of this paper is to review the comparison on revenue performance from property tax in Malaysia between rates and land tax in order to improve understanding about property tax as a whole, based on the review of literature references to local and foreign publications. The references include the annual report of various authorities, the auditor’s report on the financial, articles in newspapers, and reviews of previous research works as well as related journals. The findings revealed that there are several roles of local and state authority, whereas the efficiency of the authorities in performing their role is largely dependent on their ability to effectively collect revenues from all sources available, particularly rates and land tax. Since, for most local authorities, a large proportion of their revenue comes from rates, while for state authorities, a large proportion of their revenue comes from land tax, failure to collect rates and land tax efficiently may result in revenue shortages. The inability to collect taxes effectively make more dependent on grants provided by the states and federal authorities.